Numerical Study on Discharging Characteristics of Entangled Cluster of Particles in Particle Bed - Huang, Xiaoli; Ge, Liang; Gui, Nan; Yang, X. T.; Tu, J. Y.; Jiang, S. Y. (Frontiers in Energy Research, 2021)
To better understand the flow features of the particle cluster in a particle bed, discharging of the particle entangled cluster is simulated by the discrete element method (DEM). The particle entangled cluster is composed of eight particles connected by rigid bonds, and the simulated entangled cluster models are divided into two types: axisymmetric u-particles and distorted z-particles. The simulation starts with the closed discharge outlet, and the bonded clusters with different IDs are randomly added from the entrance section. The particles fall freely and accumulate freely in the particle bed. The discharge hole opens after all the particles are stationary for a period. Then, the particles are discharged from the particle bed under gravity. The discharging process has time-dependent bulk-movement behavior. There is not much mixing between layers on the boundary. The vertical end not only makes the packing loose but also intensifies the interaction between particles due to entanglement. Consequently, the discharge features of particle entangled clusters of different included angles were quantified. The results show that the particle discharging speeds depend on the entanglement angle (α of u-particles and η of z-particles) and discharging outlet diameter. A large included angle may play the role of retarding or inhibiting the discharging flow rate. Therefore, the entanglement of particle components also always plays the key role of retarding the discharge.